Global Migration Law in Tunisia: The Potential of the Global Compact for Migration to Support the Ratification of the United Nations Convention on Migrant Workers Rights - Younous Arbaoui; Amina Semaoui (Laws)
While Tunisia endorsed the non-binding Global Compact for Migration (GCM), it has not yet ratified the binding International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families (ICRMW). In view of the overlap and convergence between both instruments and the fact that soft and hard law interact through cross-fertilisation processes, with the result that the boundaries between both become blurred, this article examines the potential of the GCM to reinforce the legal standing of the ICRMW in Tunisia and to pave the way for the attenuation of the obstacles to its ratification. Based on policy documents, interviews and secondary sources, we first conclude that the Compact has a considerable potential to promote the Convention as it created a political dialogue in which the Convention gained attention and visibility. Crucially, the implementation of Objective 6(a) GCM, calling for ratification of international labour instruments, appears to be the first step towards ratification as it resulted in a governmental decision to re-consider the ratification of the ICRMW. Secondly, on the basis of comparative legal analysis, we conclude that reading the ICRMW’s provisions through the lens of corresponding GCM Objectives attenuates the obstacles to ratification of the ICRMW. Our findings exemplify the well-established influential function of soft law as a catalyst supporting hard law by reinforcing its legal standing and by providing an impetus for its endorsement. Both analysis and conclusions are not only relevant for the Tunisian case but also for all other countries that endorsed the GCM but have yet to ratify the ICRMW.